Relevansi Pemikiran Emanuel Levinas dalam Konteks Pandemi Covid-19 - Benyamin Molan (Center for Philosophy and Ethics, 2020)
Covid-19 as a pandemic has deeply troubled in human life. All countries around the world have been trying hard to stem the spread of this virus. Gradually, people began to realize that all efforts to prevent the spread of this virus could not be handled individually. Measures and policies such as staying at home, wearing masks, washing hands, maintaining distance (physical distancing), avoiding crowds (social distancing), are not just for the sake of saving oneself but especially for the safety of others. It is plausible that in the discourse on responsibility towards others, Levinas' thought is presented.